APLIKASI KONTROL PID UNTUK PENGATURAN PUTARAN MOTOR DC PADA ALAT PENGERING OTOMATIS KAIN BATIK PEWARNA INDIGOSOL - Alamsyah, Yahya; Siswojo, Bambang; Maulana, Eka (Jurnal Mahasiswa TEUB, 2023)
Batik is a historical heritage that can still be preserved and conserved to this day. One of the types of synthetic dyes used in batik coloring is indigosol dye. Indigosol dye is a type of water-soluble dye substance. To achieve optimal sunlight exposure, technology is needed in the form of a device that can assist in the drying process to optimize the drying results and anticipate rain. One of the technologies that can assist the industrial sector in the drying process of fabrics using indigosol is an automatic dryer. This device releases wet fabric when the weather is hot and clear, and it secures the fabric when the weather is cloudy and rain is expected or when rain suddenly falls. The use of PID control on the DC motor driving this device is used to gradually increase the speed before the first two seconds so that the hung fabric does not sway too much and burden the motor. PID control is also used to ensure a stable motor rotation before the first two seconds. This research involves several testing stages, including testing the system's response with PID control and sensor readings. Testing begins with determining the PID parameter values to be used and continues by observing the system's response to the motor values controlled by PID. Sensor readings are used to determine whether the sensor is functioning properly, and this is done by reading the sensors in the Arduino IDE application. The testing process yielded the PID parameter values: KP = 0.1 , Ki = 0.01 , Kd = 0.04. The system's response with these parameter values showed stable system performance with a delay time of 1.6 seconds, rise time of 1.6 seconds, peak time of 2 seconds, no overshoot, and a settling time of 2 seconds. Keywords: Batik, Indigosol Dye, DC Motor, PID, System Response